AN ANALYSIS OF THE EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT STRATEGY TOWARDS THE DECREASE OF OUTSTANDING CONTRIBUTIONS FOR PUBLIC MOTOR VEHICLES AT PT. JASA RAHARJA SUKABUMI REPRESENTATIVE - ABYASA; R. DENI MUHAMMAD DANIAL; ACEP SYAMSUDIN (CV KULTURA DIGITAL MEDIA, 2021)
The current era of world globalization and free trade causes an influence on business and its processes. There are many new business models and companies in various fields of goods and services that cause competition between these companies and business modelsTo achieve this, the right business strategy is needed to realize the company's targets that have been previously set. If you look at the business strategy, Customer Relationship Management (CRM) is one of the business strategies regarding the process of managing detailed information related to individual customers, and all customer contact points carefully in order to maximize customer loyalty to a business entity. Jasa Raharja as a company that has consumers in this case taxpayers and entrepreneurs / owners of public transportation also needs to communicate with its consumers, one of which is through Customer Relationship Management (CRM) activities. The role of Customer Relationship Management (CRM) here is to provide information on whether there is an influence between the Customer Relationship Management (CRM) strategy and decreasing outstanding of Iuran Wajib Kendaraan Bermotor Umum (IWKBU). The Result from this research has shown that CRM is definitely have an impact for decreasing an outstanding of IWKBU.